2004
DOI: 10.1161/01.atv.0000127083.88549.58
|View full text |Cite
|
Sign up to set email alerts
|

Stable Compounds of Cigarette Smoke Induce Endothelial Superoxide Anion Production via NADPH Oxidase Activation

Abstract: Objective-Endothelial dysfunction is an early manifestation of cigarette smoke (CS) toxicity. We have previously demonstrated that CS impairs nitric oxide (NO)-mediated endothelial function via increased generation of superoxide anion (O 2 . ). In these studies, we investigated whether stable compounds present in CS activate specific pathways responsible for the increased endothelial O 2 . production.Methods and Results-Short exposure of bovine pulmonary artery endothelial cells (BPAECs), human pulmonary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(177 citation statements)
references
References 38 publications
10
155
3
3
Order By: Relevance
“…These findings are consistent with previous findings indicating that cigarette smoke induces endothelial superoxide anion production via NADPH oxidase activation. 29 Therefore, our results demonstrate the …”
Section: Discussionsupporting
confidence: 66%
“…These findings are consistent with previous findings indicating that cigarette smoke induces endothelial superoxide anion production via NADPH oxidase activation. 29 Therefore, our results demonstrate the …”
Section: Discussionsupporting
confidence: 66%
“…8,9 Once active NADPH oxidase forms, it catalyzes the transfer of electrons from NADPH to molecular oxygen producing the superoxide anion (O 2 NADPH oxidase is the main cellular source of ROS in mononuclear and granulocytic leukocytes and is involved in host defense. 9 It has been shown that CS induces endothelial O 2 ⅐Ϫ production via NADPH oxidase activation in cell culture systems, 11,12 which was associated with CS-induced lung inflammation and injury. Recent studies have shown that NADPH oxidase subunits are under tight regulatory control in physiological conditions.…”
Section: Cigarette Smoke (Cs) Induces Recruitment Of Inflammatory Celmentioning
confidence: 99%
“…N G -nitro-L-arginine methyl ester (L-NAME), a specific inhibitor of NOS at the haem site (Pritchard et al 1995;Munzel et al 2000;Pritchard et al 2001;Stepp et al 2002) and apocynin, an inhibitor of NADPH oxidase protein complex formation (Jaimes et al 2004), were obtained from Sigma and utilized in inhibition studies.…”
Section: Additional Reagents and Materialsmentioning
confidence: 99%
“…The combined effects of NOS and NADPH oxidase in H 2 O 2 -induced increases in intracellular O 2 .-in PAEC were investigated using L-NAME, which blocks both NO and O 2 .-production by NOS (Pritchard et al 1995;Munzel et al 2000;Pritchard et al 2001) and apocynin, a pharmacological inhibitor of NADPH oxidase (Jaimes et al 2004). …”
Section: Nos and Nadph Oxidase Co-inhibitionmentioning
confidence: 99%